Registration, procurement, distribution, and use of misoprostol in Uganda: an interview-based observational study - Atukunda, Esther Cathyln; Brhlikova, Petra; Ganafa, Amon; Polloc, Allyson (Online, 2013)
Background Poor access to essential medicines remains a barrier to improvement of health in low-income countries. The maternal mortality rate from post-partum haemorrhage (PPH) in Uganda is one of the highest in the world. Uganda launched a misoprostol rollout programme for prevention of PPH in 2009, before WHO added it to the Essential Medicines List. We assessed the rollout programme in Uganda. Methods We reviewed relevant documents (WHO and Ministry of Health guidelines, registration dossier), interviewed key informants, and assessed procurement data collected from the Accessing Medicines in Africa and South Asia project (2010–13). We interviewed informants from purposively selected districts of Mbarara, Bundibugyo, Kampala, and Apac (one for each Ugandan Ministry of Health performance rank). We interviewed key informants about the introduction, registration, procurement, distribution, availability, and use of misoprostol, treatment guidelines, and human resources. Findings We interviewed 82 participants. Civil society organisations promote misoprostol rollout across Uganda as part of a larger assemblage of groups working on maternal health and had a key role in misoprostol registration with the National Drug Authority and development of clinical guidelines. Evidence-based requirements for registration, guideline development, and addition to the Essential Medicines List of Uganda were scarce. Civil society and national medical stores were procuring and distributing misoprostol to health centres 2 years before its inclusion in clinical guidelines and Uganda’s Essential Medicines List, despite the contested evidence for its eff ectiveness. Promotion and distribution of misoprostol is continued by local affi liates off ering incentives to private health-care providers promoting their programmes. Interpretation Civil society organisations accelerated misoprostol rollout in Uganda. Despite its introduction as a second choice treatment, evidence suggests an increasing trend of misoprostol procurement and availability over the medicine of choice—oxytocin. Absence of guidelines and lack of training precludes rational use of misoprostol and has ramifi cations for maternal care that need urgent evaluation.
Registration, procurement, distribution, and use of misoprostol in Uganda.
Keywords: Registration, procurement, distribution,misoprostol, Uganda